Remembering Baraka’s Dutchman: A Comparative Study of Absurd Dramaturgy on the Racial Absurdity - Wahyu Seno Aji; Anna Sriastuti (Universitas Gadjah Mada, 2023)
Dutchman belongs to Afro-American Drama. In its portraying of racial problem, Dutchman is different from other black American plays as it has largely moved to the abstract and symbolic form. While Dutchman strongly indicates segregation and a kind of open conflict with the white society, many others black literature largely focus on Black Society or family’s internal conflicts. Goes along with its abstract presentation, Dutchman tends to represent the general and ‘eternal’ blacks rather than the blacks framed in social institution such as family, job, and others. Despite common accepted classification that separates ethnic literary work as strongly political and absurd theatre as metaphysical, Dutchman’s technique is strikingly similar to the absurd where content and form/technique blends. This study is to explore the tension in The Dutchman by showing its similarities and differences from both the conventional absurd play and Black literary work and to propose possible literary and social background that explain such phenomenon, which is, a racial play that takes absurdist style or as a literary act of continuing absurdist style on the racial ground. In doing so, this study uses a comparative literature approach by comparing The Dutchman with Eugene Ionesco's The Lesson and Edward Albe's The Zoo Story. In afro-american drama, there was a time when racial conflict was a condition that created a movement to a more abstract/ symbolic form similar to the Absurd play. It’s a kind of reminder for the metaphysical dramatist, a reminder of what really matter in the real world.